Multimedia On Global Grids: A Case Study In Distributed Ray Tracing - Aljaber, Bader; Jacobs, Thomas; Nadiminti, Krishna; Buyya, Rajkumar (Malaysian Journal of Computer Science, 2007)
Grid computing, a form of distributed computing, has become a hot topic recently. Currently, there are many ways in which Grids are being used in order to enhance existing IT infrastructure to better utilize distributed resources and data. Grid technology is considered to be a very powerful solution to the problem of sharing heterogeneous resources including compute resources, data stores, and different kinds of services provided by various entities. In this paper, we look at applications that make, or could make, good use of a distributed computing environment, such as a Grid. We provide some background on a selected application, the POV-Ray ray tracer, and investigate how it can benefit from running on a Grid. We use the Gridbus Resource Broker for scheduling application tasks on a Global Grid.